2015
DOI: 10.1080/19488300.2015.1017673
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical programming approach to the fractionation problem in chemoradiotherapy

Abstract: In concurrent chemoradiotherapy, chemotherapeutic agents are administered during the course of radiotherapy to enhance the primary tumor control. However, that often comes at the expense of increased risk of normal-tissue complications. The additional biological damage is mainly attributed to two mechanisms of action, which are the independent cytotoxic activity of chemotherapeutic agents and their interactive cooperation with radiation. The goal of this study is to develop a mathematical framework to obtain d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…It was found that some of these models give rise to more complex fractionation schemes, i.e. varying doses per fraction (Bertuzzi et al 2013, Salari et al 2015, Wein et al 2000, Yang & Xing 2005. However, the role of such models to guide fractionation decisions in clinical practice has been limited.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…It was found that some of these models give rise to more complex fractionation schemes, i.e. varying doses per fraction (Bertuzzi et al 2013, Salari et al 2015, Wein et al 2000, Yang & Xing 2005. However, the role of such models to guide fractionation decisions in clinical practice has been limited.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…However in the case of active radio-sensitization effect, optimal regimens use an escalated radiation dose on treatment sessions with chemotherapy administrations to benefit from the radiosensitization mechanism. This can be compared to an earlier work by Salari et al where it was shown that radio-sensitizers may alter the optimal radiation fractionation regimens in a similar fashion [48]. The benefits of accelerated hypo-fractionation schedules was established numerically, however radio-sensitizers may postpone delivering few radiotherapy sessions until the end of therapy.…”
Section: Resultsmentioning
confidence: 91%
“…A standard approach to solving Bellman's equations with forward recursion is to discretize the state space and use a linear interpolation of appropriate discretized values to increase the accuracy of cost-to-go function estimations at intermediate state values [3,48,5]. Depending on the size of the state space, a naive implementation of this approach may be computationally intractable due to the large number of possible discretized states, known as the curse of dimensionality.…”
Section: Developing Dp Solution Methodsmentioning
confidence: 99%
See 2 more Smart Citations